Phenotypic and Resistance Patterns of Avian Pathogenic Escherichia coli Isolated from Commercial Poultry Farm - Timur, N. P. V. T.; Kristianingrum, Y. P.; Suardana, I. W.; Wibowo, M. H. (Faculty of Animal Science, IPB University, 2026)
Colibacillosis in poultry is induced by avian pathogenic Escherichia coli (APEC). No relevant studies have been extensively published in Indonesia. Colibacillosis can affect various poultry species, resulting in significant economic losses to Indonesia’s poultry industry. The efficacy of colibacillosis treatment depends on the antibiotic sensitivity of the causative pathogen. This study aims to determine the phenotypic traits, pathological pictures, and antibiotic susceptibility of APEC bacteria isolated from colibacillosis cases in commercial farms in the Special Region of Yogyakarta and Central Java. Organ samples were collected from broiler and layer chickens suspected of having colibacillosis. The results of cultured, biochemical tests, pathological examinations, pathogenicity, and hemolysis testing confirmed 21 APEC isolates. The antibiotic susceptibility of the isolates was determined against nine different antibiotics. Pathological examination revealed severe macroscopic changes, including polyserositis (perihepatitis, pericarditis, and air sacculitis), accompanied by microscopic evidence of necrosis and widespread heterophilic inflammatory cell infiltration across the lungs, cardiac pericardium, and ovaries. The resistance patterns of the samples to nine antibiotics, ranked from highest to lowest, were as follows: amoxicillin, enrofloxacin, streptomycin, trimethoprim-sulfamethoxazole, nalidixic acid, oxytetracycline, tetracycline, gentamicin, and neomycin. The highest resistance was observed against β-lactam antibiotics. The APEC isolates displayed high pathogenicity, characterized by typical gross and histopathological lesions of colibacillosis, including polyserositis. Crucially, the high prevalence of multidrug resistance (MDR) against nine tested antibiotics (71.43%), particularly to amoxicillin, poses a serious challenge to effective colibacillosis treatment in the studied regions and necessitates a strategic shift in antibiotic usage policies.